2020
DOI: 10.1101/2020.03.20.000794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Candidates: Prediction and Validation of 174 SARS-CoV-2 Epitopes

Abstract: The recent outbreak of SARS-CoV-2 (2019-nCoV) virus has highlighted the need for fast and efficacious vaccine development. Stimulation of a proper immune response that leads to protection is highly dependent on presentation of epitopes to circulating T-cells via the HLA complex. SARS-CoV-2 is a large RNA virus and testing of all overlapping peptides in vitro to deconvolute an immune response is not feasible. Therefore HLA-binding prediction tools are often used to narrow down the number of peptides to test. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 37 publications
(20 reference statements)
3
56
0
Order By: Relevance
“…The same analysis was performed for the 152 SARS-CoV-2 peptides identified by Prachar et al (Prachar et al, 2020), which are also verified by HLA binding assays to be strong binders to diverse HLA Class I molecules. Our classifier predicted that 98 of them are immunogenic (Table 1 and Supplementary Table S2).…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 64%
See 4 more Smart Citations
“…The same analysis was performed for the 152 SARS-CoV-2 peptides identified by Prachar et al (Prachar et al, 2020), which are also verified by HLA binding assays to be strong binders to diverse HLA Class I molecules. Our classifier predicted that 98 of them are immunogenic (Table 1 and Supplementary Table S2).…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 64%
“…Only a fraction of SARS-CoV-2 peptides that bind to HLA molecules are immunogenic Many research groups have identified peptides derived from SARS-CoV-2 that can bind with HLA molecules (Ahmed, Quadeer and McKay, 2020;Campbell et al, 2020;Grifoni et al, 2020;Nerli and Sgourakis, 2020;Prachar et al, 2020). Two different approaches were employed.…”
Section: Model Development and Training Against Clinical Datamentioning
confidence: 99%
See 3 more Smart Citations